2023
DOI: 10.3390/microorganisms11092256
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Structure Analysis of the Multi-Domain, Cell Envelope Proteases of Lactic Acid Bacteria

Lise Friis Christensen,
Magnus Haraldson Høie,
Claus Heiner Bang-Berthelsen
et al.

Abstract: Lactic acid bacteria (LAB) have an extracellular proteolytic system that includes a multi-domain, cell envelope protease (CEP) with a subtilisin homologous protease domain. These CEPs have different proteolytic activities despite having similar protein sequences. Structural characterization has previously been limited to CEP homologs of dairy- and human-derived LAB strains, excluding CEPs of plant-derived LAB strains. CEP structures are a challenge to determine experimentally due to their large size and attach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(175 reference statements)
0
4
0
Order By: Relevance
“…The present study explored L. amylovorus (ASV752) and S. alactolyticus (ASV5126) as the ASVs that contributed most to the dissimilarity of clusters LACTO and CSST. The evaluation of the proteolytic ability of LAB group members was of central interest in previous studies ( Liu et al, 2010 ; Kieliszek et al, 2021 ; Christensen et al, 2023 ). However, it was revealed that the proteolytic ability can vary widely ( Liu et al, 2010 ; Christensen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study explored L. amylovorus (ASV752) and S. alactolyticus (ASV5126) as the ASVs that contributed most to the dissimilarity of clusters LACTO and CSST. The evaluation of the proteolytic ability of LAB group members was of central interest in previous studies ( Liu et al, 2010 ; Kieliszek et al, 2021 ; Christensen et al, 2023 ). However, it was revealed that the proteolytic ability can vary widely ( Liu et al, 2010 ; Christensen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the proteolytic ability of LAB group members was of central interest in previous studies ( Liu et al, 2010 ; Kieliszek et al, 2021 ; Christensen et al, 2023 ). However, it was revealed that the proteolytic ability can vary widely ( Liu et al, 2010 ; Christensen et al, 2023 ). Although all members are equipped with a proteolytic system consisting of proteinases, transport proteins and peptidases, there are inter-species differences ( Kieliszek et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the cheese microbiota to flavor development characterizes the quality and recognition of the cheese and is thus of critical significance. The final cheese flavor, as with many of the final characteristics of cheese, is due to the interactions between the cheese microorganisms, the growth substrates, proteins in the milk, and the cheese environment [14,16]. During cheese manufacturing, environmental parameters such as temperature, pH, osmolarity, and lactose concentration change significantly.…”
Section: Premise: Cheeses and Their Microbiotamentioning
confidence: 99%
“…It is well established that cell lysis is a key event for the release of cytoplasmic enzymes into the cheese matrix and is crucial for understanding the contribution of different microbial cells to cheese ripening [17,[20][21][22][23][24][25][26][27][28][29][30]. In this way, the proteolysis of caseins should be considered a crucial event in determining the outcome of the process [1,7,16,31].…”
Section: Premise: Cheeses and Their Microbiotamentioning
confidence: 99%